Factors associated with survival to hospital discharge following endoscopic treatment for synovial sepsis in 214 horses. (12th January 2014) - Milner, P. I.; Bardell, D. A.; Warner, L.; Packer, M. J.; Senior, J. M.; Singer, E. R.; Archer, D. C.
Summary: Reasons for performing study: To determine risk factors involved in survival to hospital discharge of cases of synovial sepsis. Objectives: Investigate pre‐, intra‐ and post operative factors involved in short‐term survival of horses undergoing endoscopic treatment for synovial sepsis. Study design: Retrospective case series. Methods: Clinical data were obtained for horses (>6 months old) undergoing endoscopic surgery as part of management for synovial sepsis over a 7‐year period in a single hospital population. Descriptive data were generated for pre‐, intra‐ and post operative variables. Multivariable logistic regression analysis was used to develop 3 models related to presurgical, surgical and post surgical stages of management with outcome defined as survival to hospital discharge. Results: Two hundred and fourteen horses were included. In Model 1 (preoperative variables), increased preoperative synovial fluid total protein (TP) was associated with nonsurvival (OR 0.88, 95% CI 0.83–0.94, P<0.001) whereas the presence of a wound on admission was associated with survival (OR 4.75, 95% CI 1.21–18.65, P = 0.02). Model 2 (intraoperative variables) revealed that factors associated with decreased survival were anaesthetic induction outside of normal working hours (OR 0.36, 95% CI 0.15–0.88 P = 0.02) and presence of moderate/severe synovial inflammation at surgery (OR 0.28, 95% CI 0.12–0.67, P = 0.004). Model 3 (post operative variables) showed that increased post operative synovial fluid TP (OR 0.94, 95% CI 0.90–0.98, P = 0.013) and undertaking more than one endoscopic surgery for treatment (OR 0.19, 95% CI 0.05–0.70, P = 0.005) were associated with nonsurvival. Cut‐off values for predicting survival were 55–60 g/l for preoperative and 50–55 g/l for post operative TP measurements. Conclusions: This study has identified factors associated with altered likelihood of survival to hospital discharge following endoscopic surgery for synovial sepsis. Prognosis for survival to hospital discharge can be based on evidence from this study at the key stages of management of horses with synovial sepsis.